2011
DOI: 10.1128/iai.00133-11
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fibronectin-Binding Proteins A and B inIn VitroCellular Infections andIn VivoSeptic Infections by Staphylococcus aureus

Abstract: Fibronectin-binding protein A (FnBPA) and FnBPB are important adhesins for Staphylococcus aureus infection. We constructed fnbA and/or fnbB mutant strains from S. aureus SH1000, which possesses intact rsbU, and studied the role of these adhesins in in vitro and in vivo infections. In intravenous infection, all fnb mutants caused a remarkable reduction in the colonization rate in kidneys and the mortality rate of mice. fnbB mutant caused a more severe decrease in body weight than that caused by fnbA mutant. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 61 publications
4
71
0
2
Order By: Relevance
“…Indeed, although we analyzed only a small number of animals, which can limit the evaluation of the results, it is interesting the high levels of the proinflammatory cytokines IL-1␤ and IL-6 in plasma following both bolus and continuous-infusion inoculation with L. lactis expressing FnbpA, although bolus inoculation increased cytokine levels earlier than did continuous inoculation. FnbpA was previously shown to induce the production of IL-6 by endothelial cells in vitro (19,35) and to be a major player responsible for both the proinflammatory and the procoagulant endothelium responses in vivo during S. aureus endovascular infections (15,18,36). The increase in the level of IL-1␤ is in line with the findings of previous studies showing that fibronectin induces IL-1␤ gene transcription and increases IL-1␤ protein secretion in vitro (37).…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, although we analyzed only a small number of animals, which can limit the evaluation of the results, it is interesting the high levels of the proinflammatory cytokines IL-1␤ and IL-6 in plasma following both bolus and continuous-infusion inoculation with L. lactis expressing FnbpA, although bolus inoculation increased cytokine levels earlier than did continuous inoculation. FnbpA was previously shown to induce the production of IL-6 by endothelial cells in vitro (19,35) and to be a major player responsible for both the proinflammatory and the procoagulant endothelium responses in vivo during S. aureus endovascular infections (15,18,36). The increase in the level of IL-1␤ is in line with the findings of previous studies showing that fibronectin induces IL-1␤ gene transcription and increases IL-1␤ protein secretion in vitro (37).…”
Section: Discussionsupporting
confidence: 81%
“…We chose to focus on fnbA rather than fnbB because all isolates had fnbA, but only 85% of the CDI isolates possessed the gene for FnBPB (i.e., 15% of the CDI isolates had only fnbA). This distribution is similar to that reported in other studies of clinical isolates, which have found that >70% of isolates have both FnBPA and FnBPB, 20% have only FnBPA, but isolates encoding only FnBPB are rare (∼1%) (24,25). isolates.…”
Section: Resultssupporting
confidence: 74%
“…Studies with clinical isolates suggested that strains associated with invasive disease are significantly more likely to have two fnb genes (Peacock et al 2000). Molecular studies have also shown that both FnBPA and FnBPB are required for the establishment of septic infection (Shinji et al 2011). However, in S. aureus that have both homologs, deletion of either gene does not abolish fibronectinbinding capacity of the cell (Greene et al 1995).…”
Section: Org Downloaded Frommentioning
confidence: 99%